1983
DOI: 10.1093/ajcn/38.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body composition and nitrogen content of renal patients on chronic dialysis as determined by total body neutron activation

Abstract: Total body protein (nitrogen), body cell mass (potassium), fat, and water were measured in 15 renal patients on maintenance hemodialysis (MHD). Total body nitrogen was measured by means of prompt gamma neutron activation analysis; total body water was determined with tritium labeled water; total body potassium was measured by whole body counting. The extracellular water was determined by a technique utilizing the measurement of total body chloride and plasma chloride. When compared with corresponding values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Our results stand in contradistinction from a study performed several decades ago utilizing 40 K analysis in HD patients and matched controls; however, subjects were receiving regularly scheduled dialysis [15]. It is evident in the best of circumstances when patients receive maintenance HD that muscle wasting occurs in patients with ESRD, and it has been attributed to a number of metabolic changes including insulin resistance, presence of acidosis and inflammation [16,17].…”
Section: Discussioncontrasting
confidence: 62%
“…Our results stand in contradistinction from a study performed several decades ago utilizing 40 K analysis in HD patients and matched controls; however, subjects were receiving regularly scheduled dialysis [15]. It is evident in the best of circumstances when patients receive maintenance HD that muscle wasting occurs in patients with ESRD, and it has been attributed to a number of metabolic changes including insulin resistance, presence of acidosis and inflammation [16,17].…”
Section: Discussioncontrasting
confidence: 62%
“…Sophisticated techniques, such as neutron activation analysis or total body potassium, are accurate and reliable methods but are expensive and not available for clinical purposes; 39,40 anthropometric measurements also accurately re¯ect nutritional status and body composition in dialysis, 13,41 but are time-consuming and not practical to take on a routine basis. On the other hand, clinical and laboratory parameters are easy to collect but imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…As yet, studies on only small numbers of patients using this technique have been published. Cohn et al [8] found a reduction in total body protein in 15 haemodialy sis patients, but this did not reach statistical significance. Williams et al [9] found a significant 9% reduction in total body protein in 43 patients dialysed for up to 5 years, but normal values in 8 patients dialysed for over 5 years.…”
Section: Introductionmentioning
confidence: 91%